The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1063/1.1338494
|View full text |Cite
|
Sign up to set email alerts
|

He–Xe microdischarges: Comparison of simulation results with experimental data

Abstract: A comparison of predictions of a one-dimensional simulation model with the results of a recent experimental study [Appl. Phys. Lett. 76, 544 (2000)] of a dc He–Xe microdischarge is presented. The experimental results are remarkably reproduced by the model but only when unusually high values are used for the unknown rate coefficients of formation and recombination reactions of HeXe+ heteronuclear ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…We noted that for the range of current density studied (abnormal glow regime) the discharge voltages in mixtures of helium and xenon were surprisingly higher than in either pure xenon or pure helium, when the xenon fraction exceeded about 10%. While we originally attributed this to the possible formation of HeXe + ions that have lower secondary emission coefficients, Veronis and Inan 10 have modeled our specific experiment, and concluded that the required rate coefficient for the formation of this species would have to be unacceptably high. In this letter, we have revisited this problem, extending our experiments to mixtures of Xe and Ne, and to a wider range of current densities and pressures, and we show here that we can reproduce the general trends seen experimentally with a onedimensional fluid model by taking into account charge exchange process.…”
mentioning
confidence: 96%
“…We noted that for the range of current density studied (abnormal glow regime) the discharge voltages in mixtures of helium and xenon were surprisingly higher than in either pure xenon or pure helium, when the xenon fraction exceeded about 10%. While we originally attributed this to the possible formation of HeXe + ions that have lower secondary emission coefficients, Veronis and Inan 10 have modeled our specific experiment, and concluded that the required rate coefficient for the formation of this species would have to be unacceptably high. In this letter, we have revisited this problem, extending our experiments to mixtures of Xe and Ne, and to a wider range of current densities and pressures, and we show here that we can reproduce the general trends seen experimentally with a onedimensional fluid model by taking into account charge exchange process.…”
mentioning
confidence: 96%